1995
DOI: 10.1530/jrf.0.1050263
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic treatment with a gonadotrophin-releasing hormone agonist on peripheral concentrations of FSH and LH, and ovarian function in heifers

Abstract: The effect of chronic treatment with a gonadotrophin-releasing hormone agonist (GnRHa) on ovarian function in cattle was investigated by injecting heifers i.m. twice a day with saline, 5 micrograms GnRHa (Buserelin) or 10 micrograms GnRHa (n = 7) for 21 days. Blood samples were taken twice a day during the treatment period, and then three times a day for 7 days and once daily for a further 4 days. Frequent samples were also collected on day 1, day 10 and day 21 of treatment. The ovaries of all heifers were exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
44
1
5

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(61 citation statements)
references
References 4 publications
11
44
1
5
Order By: Relevance
“…The concentrations of FSH, similar to those observed in other studies (Adams et al, 1994;Gong et al, 1995), varied according to the day of the cycle, although no difference between days resulted from the nutritional treatment in the total concentration of this hormone (P>0.05). Similarly, LH showed no difference between the treatments (P>0.05) ( Table 2).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The concentrations of FSH, similar to those observed in other studies (Adams et al, 1994;Gong et al, 1995), varied according to the day of the cycle, although no difference between days resulted from the nutritional treatment in the total concentration of this hormone (P>0.05). Similarly, LH showed no difference between the treatments (P>0.05) ( Table 2).…”
Section: Resultssupporting
confidence: 88%
“…These data indicate that the increased intake of energy affects the recruitment of smaller follicles but does not alter the dominant follicle in Bos indicus animals, as previously observed by Gutierrez et al (1997) and Armstrong et al (2002) in Bos taurus. Some studies have demonstrated the increased number of smaller follicles in Bos taurus in response to increasing the amount of energy consumed or the application of GH (Gong et al, 1991), but few data are shown in Bos indicus. In a previous study, Maurasse et al (1985) demonstrated that changes in the nutritional plan produced changes in the appearance of follicles of various sizes and a sharp increase of the follicles in cattle, as partially observed in this experiment.…”
Section: Resultsmentioning
confidence: 99%
“…This may be accompanied by a reduction or maintenance of basal LH concentrations. Basal LH concentrations are reduced in women (Shaw et al 1985) and macaques , while in marmosets (Lunn et al 1992) and heifers (Gong et al 1995, Bergfeld et al 1996 basal LH concentrations remain unchanged. Despite the variable effects on basal LH, the preovulatory LH surge appears to be universally inhibited, as is ovulation.…”
Section: Introductionmentioning
confidence: 94%
“…The repeated treatment with GnRH-A has been reported to suppress pulsatile secretion of LH and block the development of dominant follicles [7]. These resulted in the prevention of preovulatory LH surge and ovulation in heifers [7].…”
mentioning
confidence: 99%
“…These resulted in the prevention of preovulatory LH surge and ovulation in heifers [7]. In the absence of pulsatile LH secretion, FSH stimulates the growth of large and estrogenic follicles which, when stimulated, ovulate to produce viable corpora lutea in the ewe [16].…”
mentioning
confidence: 99%